CITIZENFOUR: INTERNET PUBLICS AND THE IMAGINARY OF PRIVACY A CONTENT ANALYSIS OF TWITTER COMMENTARIES AROUND THE 2015 OSCAR WINNING DOCUMENTARY - Boccia Artieri, Giovanni; Giglietto, Fabio; Gemini, Laura (AoIR Selected Papers of Internet Research, 2015)
The aim of the paper is to analyze the Twitter conversations produced by networked publics of the Laura Poitras’s documentary Citizenfour (2014). The documentary deals with the case of the computer analyst Edward Snowden and it was aired by HBO in USA and Channel 4 in UK respectively the 23th and 25th of February 2015. We focused on the type of representations produced around the relationship between privacy and the Internet, ie the imaginary related to privacy conveyed by Snowden case. The paper thus attempt to answer the following RQ: what are the privacy’s imagery around Snowden case emerging from double screen audience of documentary Citizenfour? Based on a complete corpus of 25,000 tweets containing the hashtag #citizenfour and created between 22th and 26th of February 2015, the research identified peaks in the Twitter activity (through a ‘breakout detection’) as well as what accounted for those peaks (through a semantic cluster analysis). Finally, a sample of original tweets will be content analyzed using a codeset derived by DeCew (1997) definitions in order to identify the emerging imaginary of privacy.